EMERGENCY OPERATION MODES OF ELECTRICAL INSTALLATIONS - IGNITION SOURCES IN OLD BUILDINGS - Беспалова, Алла; Романюк, Василий; Дашковская, Ольга; Кныш, Алексей; Чумаченко, Татьяна (SWorldJournal, 2024)
An analysis of the emergency operation of electrical networks in old buildings was carried out, in which the saturation of the premises with technical life support systems increased greatly, as a result of which the load of electrical networks increased,